2014
DOI: 10.1021/nn406360w
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Reabsorption Doped-Nanocrystal Luminescent Solar Concentrators

Abstract: Optical concentration can lower the cost of solar energy conversion by reducing photovoltaic cell area and increasing photovoltaic efficiency. Luminescent solar concentrators offer an attractive approach to combined spectral and spatial concentration of both specular and diffuse light without tracking, but they have been plagued by luminophore self-absorption losses when employed on practical size scales. Here, we introduce doped semiconductor nanocrystals as a new class of phosphors for use in luminescent sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
240
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(249 citation statements)
references
References 57 publications
5
240
0
2
Order By: Relevance
“…For example, in Mn-doped ZnSe/ZnS core/shell NCs, small amount (0.1-1%) of Mn 2+ introduces new localized excited energy states within the bandgap of ZnSe resulting in exhibit enhanced downshifted luminescence. [9] Ternary or quaternary compound semiconductors are also introduced in core/shell QDs, such as CdSe/Cd x Pb 1-x S [73] and CuInSe x Se 2-x /ZnS QDs. [12] Among quantom dot emitters, a new class of emitter materials has been reported recently based on 0D nanoclusters and nanocluster nanocrystals for these applications.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Mn-doped ZnSe/ZnS core/shell NCs, small amount (0.1-1%) of Mn 2+ introduces new localized excited energy states within the bandgap of ZnSe resulting in exhibit enhanced downshifted luminescence. [9] Ternary or quaternary compound semiconductors are also introduced in core/shell QDs, such as CdSe/Cd x Pb 1-x S [73] and CuInSe x Se 2-x /ZnS QDs. [12] Among quantom dot emitters, a new class of emitter materials has been reported recently based on 0D nanoclusters and nanocluster nanocrystals for these applications.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…[3] This work has been subsequently followed by a number of other groups. [8][9][10][11][12] In contrast to transparent photovoltaics, which have also been developed to exploit this untapped area, [13][14][15] this new concentrator approach offers an alternative pathway whereby energy is transported optically, offering a simple route to large-area manufacturing, high defect tolerance, angle independent performance, and low-level energy cost. In this progress report we discuss the theoretical limits of transparent LSCs, idealized configurations, scalability, and properties of enabling materials.…”
mentioning
confidence: 99%
“…Recently it has been showed that Mn 2+ -doped ZnSe nanocrystals can work as phosphors that show no luminescence reabsorption for use in LSCs [38] (Fig. 5b).…”
Section: Luminescent Solar Concentratorsmentioning
confidence: 99%
“…Another demonstration used Mn 2+ -doped ZnSe/ZnS core-shell CQD structures in a LSC system [268]. Due to a large difference in the absorptivity between the Mn 2+ ion inclusions and the ZnSe, a Stokes shift of 1 eV was obtained.…”
Section: Luminescent Solar Concentratorsmentioning
confidence: 99%